Association between sleep duration and myopia among young school-aged children - Junjie LIU; Zhanghao ZHU; Yangrundong FANG; Weiwei ZHOU (Guangxi Yike Daxue xuebao)
Objective To explore the association between myopia and sleep duration among young school-aged children in Xixiangtang District, Nanning City, Guangxi. Methods A total of 1, 682 school-aged children aged 6 to 9 years who were treated at the Optometry Center of the Second Affiliated Hospital of Guangxi Medical University from September 2020 to March 2022 were selected as the research subjects. They underwent distant vision examination, refractive examination and questionnaire survey. They were divided into myopia group (737 cases) and non-myopia group (945 cases) based on whether they had myopia. Logistic regression analysis was used to analyze the association between sleep duration and myopia in young school-aged children. Results In this survey, the overall prevalence of myopia among young school-aged children was 43.82%, with 40.19% of these children having a nocturnal sleep duration of 9 hours or more. The results of the univariate analysis showed that there were significant differences between the two groups of students in terms of age, parental myopia status, nap duration exceeding 1 hour, waking up between 6:31 and 7:00, nocturnal sleep duration of at least 9 hours, and total sleep duration of at least 10 hours (P < 0.05). However, there were no statistically significant differences in terms of gender and nighttime sleep onset time between the two groups (P > 0.05). Multivariate analysis showed that age and parental myopia were significantly associated with myopia in children (P < 0.05), while nap duration, morning wake-up time, nocturnal sleep duration and total sleep duration were not significantly associated with the prevalence of myopia (P > 0.05). Conclusion There is no significant association between sleep duration and myopia in young school-aged children. The prevention and control of myopia among young school-aged children should place more emphasis on the management of myopia risk factors.